The values of ex-ante and ex-post communication in dictator games - Pascal Langenbach (Max Planck Institute for Research on Collective Goods, 2016)
In the dictator game, the recipient's opportunity to send a message to the dictator increases giving. This paperreports two experimentswhich study how the timing of messages affects dictators' decisions (experiment 1) and which value recipients attach to communication opportunities (experiment 2). The first experiment shows that the effect of communication on dictator giving is equally strong when the recipient can send a message before or after the dictator has decided. However, recipients in a second experiment reveal a strong preference for pre-decision messages: Their willingnessto pay for pre-decision messages is higher than for post-decision messages.
Keywords: D63; D64; C91; D83; 330; communication; altruism; inequality; dictator game